Multi-Roles Based Pada Rancang Bangun Surat Dengan Metode Rapid Application Development (RAD) : ( Studi Kasus : Perjalanan Dinas Dilingkup Dinas TPHP Kabupaten Magetan ) - Teresa Puji Astuti; Latjuba Sofyana; Alim Citra Aria Bima (CV. ITTC INDONESIA, 2025)
Official travel is a crucial activity for government agency employees, including the TPHP Office of Magetan Regency, in carrying out assigned duties. The TPHP Office is responsible for improving performance through inter-unit collaboration. However, official travel management is still conducted conventionally using Microsoft Word for documents such as travel assignment letters (SPT) and travel reports. This approach often leads to formatting and writing errors, slowing down administrative processes. Manual management poses risks of human error, including duplicate numbering and budget miscalculations. Therefore, a web-based application is needed to enhance control and management of official travel, including SPD administration and accommodation expenses. This study aims to design and implement a web-based Official Travel Document Management application for the TPHP Office of Magetan Regency. The RAD method was used for application development, with system testing conducted through functional testing and user acceptance testing. The functional testing results showed a 99.01% compliance rate, with a 0.99% non-compliance rate. User acceptance testing results covered four categories: appearance (83.08% - good), ease of use (86.41% - very good), flow (86.41% - very good), and functionality (89.81% - very good). This application is expected to improve the efficiency and effectiveness of official travel management.